Control interno administrativo del centro de educación básica "Juan Antonio Vega Arboleda", cantón El Carmen. período 2011 - Alcívar Acosta, María Monserrate (2013)
Research "Juan Antonio Vega Grove", developed in basic education center located in the 52 km, via Quevedo - Sto Domingo, canton and parish El Carmen Manabí province. With the following geographical coordinates are: 0º 43´16 ' South latitude and 79 ° 27´00 ' West longitude. The investigative process lasted for 30 days. The results were: according to the diagnosis of the basic education center "Juan Antonio Vega Arboleda" via the workflow processes has allowed to know that the entity does not have internal policies to benefit the entire organization.According to the assessment of the internal control of basic education center "Juan Antonio Vega Grove", in the address area shows 60% which represents a level of confidence not so in the area of subdivision with 33%, collections Office with the 59.09% and secretariat with the 58.33% presented a medium control. Because controls are deficient effect caused in the administrative processes in the period 2011, it is that they cannot fulfill or perform activities efficiently. Basic Education Center "Juan Antonio Vega Arboleda" does not have a manual of policies and procedure of internal administrative control in the period 2011. Determined on internal control "Juan Antonio Vega Grove", generally held at the Centre for basic education was obtained a medium level of confidence so it rejects the hypothesis that says: evaluation of internal administrative control determines a level of confidence low in the administrative areas of basic education center "Juan Antonio Vega Arboleda", so the application of suitable administrative procedures is necessary. Research "Juan Antonio Vega Grove", developed in basic education center located in the 52 km, via Quevedo - Sto Domingo, canton and parish El Carmen Manabí province. With the following geographical coordinates are: 0º 43´16 ' South latitude and 79 ° 27´00 ' West longitude. The investigative process lasted for 30 days. The results were: according to the diagnosis of the basic education center "Juan Antonio Vega Arboleda" via the workflow processes has allowed to know that the entity does not have internal policies to benefit the entire organization.According to the assessment of the internal control of basic education center "Juan Antonio Vega Grove", in the address area shows 60% which represents a level of confidence not so in the area of subdivision with 33%, collections Office with the 59.09% and secretariat with the 58.33% presented a medium control. Because controls are deficient effect caused in the administrative processes in the period 2011, it is that they cannot fulfill or perform activities efficiently. Basic Education Center "Juan Antonio Vega Arboleda" does not have a manual of policies and procedure of internal administrative control in the period 2011. Determined on internal control "Juan Antonio Vega Grove", generally held at the Centre for basic education was obtained a medium level of confidence so it rejects the hypothesis that says: evaluation of internal administrative control determines a level of confidence low in the administrative areas of basic education center "Juan Antonio Vega Arboleda", so the application of suitable administrative procedures is necessary.